2021
DOI: 10.3889/oamjms.2021.7841
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effectiveness of Tai Chi Exercises for Improving Balance and Lower Limb Muscle Strength of the Elderly in the Community

Abstract: BACKGROUND: Balance disorders are the primary cause of falls, a significant health concern for the elderly. Tai Chi (TC) improves the balance and strength of the lower limb muscles that focus on centering the mind, bodywork, and breathing exercises. AIM: A systematic review was conducted to search for evidence of the effects of Thai Chi in balancing and strengthening of lower extremities among the elderly in the community. METHODS: According to the preferred reporting items for systematic reviews and meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In a study examining the effects of Taichi on the lower limbs of practitioners, Bagiartana and Huriah [ 53 ] conducted a systematic review and meta-analysis of the evidence regarding the effects of Taichi on balance and lower limb strength in community-dwelling older adults. The results indicated that Taichi exercise can effectively improve both balance and lower limb muscle strength in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining the effects of Taichi on the lower limbs of practitioners, Bagiartana and Huriah [ 53 ] conducted a systematic review and meta-analysis of the evidence regarding the effects of Taichi on balance and lower limb strength in community-dwelling older adults. The results indicated that Taichi exercise can effectively improve both balance and lower limb muscle strength in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was statistically significant [14]. Alternative workouts like Tai Chi, which improved balance and gained popularity, were also available [15]. Similar to standard methods of balance training, Tai Chi helps seniors enhance their ability to balance while moving [16].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors are intrinsic: related to an individual, and irrelevant: related to the environment. According to Bagiartana and Huriah [9], balance disorders in adults are the primary cause of falls, a significant health concern for older adults. Older people in nursing homes and hospitals also experience falls, which have multifactorial etiology.…”
Section: Introductionmentioning
confidence: 99%